THE SCIENTIFIC DISCUSSION OF KEY ISSUES FACTORS OF CHARACTERISTICS OF MEDICATION TOXICITIES DIFFERENCES BASED ACCORDING GENDER, PREGNANCY AND AGE, AND PHARMACOTHERAPY RISK FACTORS INFLUENCE FEATURES IN GENERAL Nana Gorgaslidze - Nana Gorgaslidze; Nodar Sulashvili; Shafiga Topchiyeva (Theoretical Hypotheses and Empirical Results, 2023)
The aim of the research was to study key issues factors of characteristics of medication toxicities differences based according gender, pregnancy and age, and pharmacotherapy risk factors influence features in general. Modern highly effective medicines are successfully used for the prevention and treatment of various diseases. Side effects of the drug can occur both when the dose is exceeded and when it is used in therapeutic doses, and with polytherapy, an absolute overdose (when taking a very large dose) and a relative overdose (when the dose is increased) are observed. The therapeutic dose of drug and the concentration in the blood should monitoring, which is associated with the pharmacokinetics of the dose of drug for a given patient peculiarity. In case of overdose, a significant increase in the main and toxic effects of the drug is observed. For example, when an overdose of vasodilators occurs, collapse occurs, when taking stimulants - convulsions, when taking sleeping pills - anesthesia, etc. The widespread use of psychotropic drugs has created a very serious problem of drug addiction. Drug addiction develops to narcotic analgesics, cocaine, sleeping pills, ethyl alcohol, tranquilizers, some stimulants, herbal preparations of hashish, marijuana, opium and others. So, the experiment revealed that there is a certain relationship between the amount of medication taken and the frequency of side effects. In geriatric practice, side effects of drugs are observed twice as often as in younger patients. In many cases, medical error caused by ignoring the side effects of the drug is due to underestimation of age-related changes. In the pharmacokinetic analysis of the drug, it is known that older people are characterized by a decrease in body weight: decrease in the amount of water in the body volume and muscle mass, which reduces the distribution of the drug in the body, reduces the metabolic functions of the liver, reduces the degree of binding of blood to plasma proteins, blood supply to vital organs, homeostatic mechanisms weaken, the level of the disease increases, which leads to the prescription of drugs of various pharmacological groups. In older people, there is a decrease in the activity of the endoplasmic reticulum of the liver. As long as the liver effectively tolerates increased concentrations of the drug that is not bound to proteins, its toxicity does not manifest itself. With a decrease in the metabolism of drugs in the liver, drug intoxication develops in older people. Therefore, as you age, it is necessary to reduce the dosage of certain medications so that the detoxification function of the liver decreases.